فعالية الرقابة الجبائية في مكافحة التهرب الضريبي في الجزائر - شافعي, عبدو; سلطاني, سمير (جامعة الوادي - University of Eloued, 2022)
لهدف من هذه الدراسة هو ابراز مدى فعالية الرقابة الجبائية في مكافحة التهرب الضريبي الذي يعتبر من أكثر الجرائم الاقتصادية والمالية شيوعا في العالم عامة وفي الجزائر خاصة، وبعد تحليل بيانات احصائية لبواقي التحصيل خلال الفترة 2017-2019 وأشكال الإجراءات الرقابية المتخذة من طرف الادارة الجبائية لتحصيل الديون الجبائية خلال هذه الفترة توصلنا الى أن الإجراءات غير الردعية المتخذة من طرف الإدارة الجبائية لتحصيل الحقوق الضريبية شجعت بعض المكلفين على التماطل في تسديد التزاماتهم الجبائية وارتفاع مبالغ بواقي التحصيل وبلوغ التهرب الضريبي مستويات قياسية في الجزائر. The aim of this study is to highlight the extent of the effectiveness of fiscal control in combating tax evasion, which is one of the most common economic and financial crimes in the world in general and in Algeria in particular, and after analyzing statistical data for the remainder of collection during the period 2017-2019 and the forms of control measures taken by the fiscal administration to collect tax debts. During this period, we concluded that the non-deterrent measures taken by the tax administration to collect tax rights encouraged some taxpayers to delay paying their tax obligations, and the amounts left over from collection increased and tax evasion reached record levels in Algeria.
The effectiveness of fiscal control in combating tax evasion in Algeria
مقال
Keywords: الرقابة الجبائية ; الإدارة الجبائية ; التهرب الضريبي ; الجهاز الرقابي ; التحصيل الضريبي